FIGURE 28. A–D in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 28. A–D, Laleonectes vocans (A. Milne-Edwards, 1878). A, B, Male, cl 11.2 mm, cw 23.6 mm (MZUSP 40174). Note stridulating ridge (arrows) stretching along the lateral walls of the carapace, across the pterygostomial region into the infraorbital margin. C, D, Male, cl 10.2 mm, cw 20 mm (MZUSP 40179). Habitus, dorsal (A, C) and ventral views (B, D). Photographs by A. Pol. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 55, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155